1997
DOI: 10.1677/joe.0.1540285
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen increases in vivo leptin production in rats and human subjects

Abstract: The decrease in estrogen in menopausal women increases body fat. The present studies were undertaken to investigate the involvement of estrogen in leptin production in vivo. In the first study, expression of ob gene mRNA in white adipose tissue was measured at 2 and 8 weeks after ovariectomy in rats. In the second, serum leptin concentration was measured in total body fat of 87 weight-matched human subjects (29 men, 29 premenopausal and 29 postmenopausal women). In the third, changes in serum leptin concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
274
7
18

Year Published

1998
1998
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 437 publications
(324 citation statements)
references
References 0 publications
25
274
7
18
Order By: Relevance
“…Studies in vitro and in vivo would suggest that sex steroids are directly responsible for the gender difference, with a direct inhibitory effect of testosterone on leptin in humans 18,19 and an increase in response to oestrogen in humans and rats. 20 Other researchers also show a higher leptin concentration in female mice, 21 however one study in rats has documented a reversal in the sexual dimorphism. 22 Leptin concentrations did not fall during this relatively shorting period of fasting, however we were able to demonstrate a rapid increase in concentrations within hours of refeeding, similar to that seen in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in vitro and in vivo would suggest that sex steroids are directly responsible for the gender difference, with a direct inhibitory effect of testosterone on leptin in humans 18,19 and an increase in response to oestrogen in humans and rats. 20 Other researchers also show a higher leptin concentration in female mice, 21 however one study in rats has documented a reversal in the sexual dimorphism. 22 Leptin concentrations did not fall during this relatively shorting period of fasting, however we were able to demonstrate a rapid increase in concentrations within hours of refeeding, similar to that seen in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Circumstantial evidence suggests that ovarian hormones affect leptin production. Leptin is reported to fluctuate with the menstrual cycle (Shimizu et al, 1997), and premenopausal HRT may regulate leptin concentrations (Augoulea et al, 2005). However, our data indicated that there was no significant difference in the average duration between the date of last menstruation and the date of enrolment between premenopausal cases and controls (25.5 vs 26.5 days), and this average duration was not significantly associated with circulating leptin levels (the Spearman correlation coefficient in the control group was 0.0823; P ¼ 0.8361).…”
Section: Discussionmentioning
confidence: 99%
“…Ovariectomy in adult rats causes a significantly decline in circulating leptin concentrations that is reversed by estradiol supplementation. 24 Circulating plasma leptin concentrations, normalized to body mass index (BMI) (a surrogate indicator of fat mass), are significantly increased in hypogonadal compared to eugonadal men, and leptin concentrations are lowered in hypogonadal men following administration of testosterone. 25 Administration of estradiol and cyprotereone acetate (an androgen receptor antagonist) to transsexual males increases circulating plasma leptin concentration (160 -180%) while administration of testosterone to transsexual females increased body weight and decreases circulating leptin concentration (750 -60%).…”
Section: Discussionmentioning
confidence: 99%